A 28 nm 512 Kb adjacent 2T2R RRAM PUF with interleaved cell mirroring and self-adaptive splitting for high density and low BER cryptographic key in IoT devices. (October 2022) - Yang, Jianguo; Lin, Ruijun; Zhou, Keji; Zhang, Yuejun; Xue, Xiaoyong; Lv, Hangbing
Abstract: This paper elaborates a 2-transistor -2-resistor (2T2R) RRAM PUF scheme with assisting circuit techniques for dense and reliable cryptographic key generation and storage. The set time mismatch in two adjacent RRAM devices is utilized to enhance the tolerance of PUF output for against PVTA variations. Array architecture with interleaved cell mirroring further improves the randomness by eliminating the systematic deviation. Self-adaptive write with current limiter eliminates the negative effect of mismatch in the peripheral circuits and suppresses the undue duration of large operation current. Double-ended differential sensing brings robustness against side-channel attacks and less voltage stress on RRAM cells. Silicon data from a 512 Kb RRAM PUF test chip in 28 nm technology demonstrates our PUF passes NIST test with intra-chip Hamming distance (HD) of <10 −5 and inter-chip HD of 0.496, and the BER is < 10 −5 from 0 to 120 °C. The proposed PUF also supports reconfigurability with good randomness and improved efficiency, featuring good resilience against machine learning attacks.